INSECTS AND MITES ASSOCIATED WITH YELLOW-BELLS IN THE COUNTY OF LONDRINA, PARANÁ, BRAZIL, WITH POTENTIAL TO ITS BIOLOGICAL CONTROL - SIMÕES, Homero Christoval; MENEZES JR, Ayres de Oliveira; DALBERTO, Fernanda Maura Sassiotti (Scientia Agraria, 2009)
The objective of this work was to identify the insects and mites associated to Tecoma stans with the greatest potential for its biological control, and to study their population dynamics in the field. Collections were carried out in the county of Londrina,Paraná, Brazil, from November 2002 to October 2003. Sampling occurred quarterly, using 10 plants, and adopting the visual inspection and the yellow sticky trap to capture the insects. Several orders were caught, especially the Hemiptera, with 48,9 % of the total specimens caught. Eulepte sp. (Lepidoptera: Pyralidae) and Tetranychus Iudeni (Acari: Tetranychidae) were the most destructive species, showing 45,3 % and 15,4 % of frequency in the inspection analysis, being considered accessory species. Eulepte sp. larval population density peak was observed in the end of March, with an average of 7,6 larvae per plant. The number of T. Iudeni adults showed great variations throughout the period under study, reaching an average of 35 adults per plant in the end of January. Several Eulepte parasites were obtained from larvae collected in the field and the two more numerous species belonging to the Braconidae family (Hymenoptera). Eulepte sp. larval population fluctuation correlated positively with the temperature but not with precipitation. The population of T. Iudeni showed no significant correlation with the weather conditons studied.